California State College at Hayward Catalog 1966 - 1967 - California State College, Hayward:::::: (1966)
A catalog of courses offered by California State College at Hayward for the academic year 1966-1967. Includes academic calendar, history of the college, names of faculty and administrators, and descriptions of courses and degrees offered.